Optimizing Project Time Management Using the Critical Path Method (CPM) and Program Evaluation and Review Technique (PERT) - Ridwan, Ahmad (Universitas Hang Tuah, 2025)
This study aims to examine the application of the Critical Path Method (CPM) and Program Evaluation and Review Technique (PERT) in optimizing project time management. The research method used is a literature study by analyzing various scientific references related to CPM and PERT. The results show that CPM is effective in identifying the critical path of a project that directly impacts project duration, while PERT excels in managing project time uncertainty through a probabilistic approach. The analysis indicates that combining both methods can enhance the accuracy of project time planning, minimize delay risks, and ensure optimal resource utilization. The conclusion of this study is that CPM and PERT have their respective advantages in project time management, and their simultaneous application can be an effective strategy for achieving project objectives more efficiently. Therefore, project managers are advised to understand the project characteristics and select the appropriate method to optimize project time management.